EXPLORING PETASE: A PROMISING ENZYME FOR PLASTIC WASTE MANAGEMENT - Vidya A.S (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Plastic pollution is a pressing global challenge owing to the pervasive, near-unmanageable threat it poses to living and non-living systems and the environmental stress it causes. The widespread use of plastic materials, their slow degradation rates, and their ability to travel vast distances through air and water currents have made plastic waste a significant environmental challenge. Plastics are classified as degradable and non-degradable ones based on their extent of degradation in natural environments. Conventional plastics, have an extremely slow degradation rate in the environments. Degradation of plastics by environmental microbes are fast, eco-friendly and minimises pollution. This study focuses on role of PETase in PET plastic degradation. Conventional methods such as photochemical, thermal are employed. Biological method using microbes provide greener solutions. Mutagenesis of marine hydrocarbonoclastic bacterium Pseudomonas aestusnigri showed PET degrading potential. The Ideonella sakaiensis mutant showed 3-fold increase in PET degradation compared to wild type. Two strains C. reinhardtii CC-124 and CC-503 degraded PET completely to terephthalic acid detected using HPLC. The in vitro technique of plastic degradation does not fit industrial applications. Thus, genetically engineered microorganisms combined with plastic-degrading enzymes would be a possible for practical application.